If at first you don't succeed: the development of climate change legislation in Ireland. Issue 2 (3rd April 2017) - Torney, Diarmuid
ABSTRACT: Ireland's national climate law, the Climate Action and Low Carbon Development Act, was enacted in December 2015. It forms part of a broader trend of countries enacting overarching national framework climate change legislation, with the UK Climate Change Act of 2008 considered to be the pioneering legislation. This article seeks to answer two questions. First, to what extent did Irish policy-makers and other stakeholders draw explicitly on the example of the UK Climate Change Act in developing the Irish climate law? Second, to what extent was the development of the climate law in Ireland characterised by convergence towards the UK Climate Change Act, and how can we explain the observed level of convergence? Using a framework drawn from policy diffusion studies, the article argues that the development of Irish climate legislation can be characterised as partial policy diffusion from UK. The broad concept of overarching national climate legislation travelled from the UK, as did certain limited design features. However, domestic politics – in particular vigorous lobbying by business and farming groups – and divergent circumstances constrained the process of policy diffusion.